2020
DOI: 10.1172/jci134485
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-induced excess of 17-hydroxyprogesterone promotes hyperglycemia through activation of glucocorticoid receptor

et al.

Abstract: dent-Newman-Keuls test was used to compare more than 2 groups. P values of less than 0.05 were considered statistically significant. Study approval. The human study was approved by the Human

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 72 publications
(79 reference statements)
0
25
0
Order By: Relevance
“…The slightly diverging observations could be due to differences in ethnicity, lifestyle factors, socioeconomic status, and sample size between the populations. A recent study in men and women by Lu et al 9 reported positive correlations between 17-OHP and fasting glucose, 2hG, and HbA 1c . This was consistent with our observations of a positive association between fasting glucose and 17-OHP among women.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The slightly diverging observations could be due to differences in ethnicity, lifestyle factors, socioeconomic status, and sample size between the populations. A recent study in men and women by Lu et al 9 reported positive correlations between 17-OHP and fasting glucose, 2hG, and HbA 1c . This was consistent with our observations of a positive association between fasting glucose and 17-OHP among women.…”
Section: Discussionmentioning
confidence: 92%
“…This was consistent with our observations of a positive association between fasting glucose and 17-OHP among women. However, the study by Lu et al 9 performed correlation analyses without appropriate confounder adjustments, therefore limiting its interpretability. A Swedish longitudinal study (n=240) conducted among opposite-sex twins found no association between progesterone and diabetes risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucocorticoid receptor (GR) of hepatocyte is found critical for both direct and indirect transcriptional regulations of IR, hyperglycemia, gluconeogenesis and fatty liver [ 19 ]. A recent study targeting 17-hydroxyprogesterone (17-OHP), an intermediate product of steroid synthesis, pointed out the involvement of hepatic Cyp17A1/17-OHP/GR pathway in the development of IR [ 20 ].…”
Section: Introductionmentioning
confidence: 99%